Childhood cirrhosis, hepatopulmonary syndrome and liver transplantation - Tumgor, Gokhan; Arikan, Cigdem; Yuksekkaya, Hasan Ali; Cakir, Murat; Levent, Erturk; Yagci, Rasit Vural; Kilic, Murat; Aydogdu, Sema (Pediatric transplantation, 2008)
:  Objectives:  The hepatopulmonary syndrome (HPS) is characterized as a triad: liver disease, intrapulmonary vascular dilatatiton, and arterial hypoxemia. The aim of this study is to analyze outcome of children with HPS in liver transplant era. Methods:  Between September 1996 and November 2006, 172 cirrhotic patients (median age 5 years; range 0.2–22 years, M/F; 97/75) were followed at Ege University Pediatric Gastroenterology, Hepatology and Nutrition Unit. All patients were evaluated by chest radiography, arterial blood gas analysis, and alveolar‐arterial oxygen tension difference, contrast echocardiography (CEE) after and before the liver transplantation. Results:  HPS was diagnosed in 33 patients (19%) by CEE. None of them had pulmonary hypertension. HPS was not found related to etiology of the liver disease. Portal hypertension was found related to the development of HPS (75.7% in patients with HPS and 54.6% in others, p = 0.02). 17 of 33 patients with HPS underwent liver transplantation. Preoperative and postoperative period of these patients was uneventful. Patients were extubated in the operating room except for two. Median follow up of transplanted children was 1.9 year (range; 0.75–10 years). Arterial blood gas analysis and CEE positivity regressed in all of them by postoperative 6th month. Conclusions:  HPS is a serious and important complication of cirrhotic children that leads to tissue hypoxia and central cyanosis. HPS seems reversible after liver transplantation in all patients.